PENGARUH SIKAP TERHADAP KEMAMPUAN PEMAHAMAN GEOMETRIS SISWA KELAS VII MELALUI REALISTIK MATHEMATIC EDUCATION BERBANTUAN SOFTWARE GEOMETER’S SKETHPAD - Marchasan Lexbin Elvi Judah Riajanto (IKIP Siliwangi, 2020)
Articles m The study of continuous learning innovations is carried out on the awareness of the complexity of educational problems. It is a reference that underlies the purpose of this study. With thirty-six students in Class VII from the medium-low cluster education unit in the area, grouped in groups of low to medium and high mathematical abilities based on the ability to understand mathematical prerequisite material, intends to see the relationship between students' positive attitudes which is the impact of innovative treatment imposed, on the ability geometrical understanding achieved by students. With the help of SPSS 17, the findings lead to the conclusion that variations in students 'attitudes towards mathematics and learning are not exactly correct or cannot be explained by the achievement variables of students' geometric understanding abilities in all three groups of mathematical abilities, low moderate and high. There are other variables that influence the achievement of the geometric ability of students in class VII. Because the students' attitude toward mathematics and positive learning is not the dominant variable that does not even have a real effect.